2017
DOI: 10.1590/s1806-92902017000100008
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic association between feed efficiency and feeding behavior, growth and carcass traits in Senepol cattle

Abstract: -The objective of this study was to evaluate the associations between feed efficiency and feeding behavior, growth and carcass traits in Senepol cattle. A total of 137 animals were evaluated. Of these animals, 36 males were evaluated in a second test, totaling 173 records (initial age of 466±96 days and initial weight of 426±104 kg). Residual feed intake (RFI) was calculated as the difference between observed and expected dry matter intake, estimated by regression of dry matter intake on average daily gain and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…These authors found that, respectively, 22% and 18% of the variation in RFI was explained by feeding events. Nkrumah et al (2007) and Guimarães et al (2017) also observed a positive correlation between feeding duration and RFI. In Bos indicus, Gomes et al (2013) also observed less feeding time, and less time standing and more time lying, for more efficient animals.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…These authors found that, respectively, 22% and 18% of the variation in RFI was explained by feeding events. Nkrumah et al (2007) and Guimarães et al (2017) also observed a positive correlation between feeding duration and RFI. In Bos indicus, Gomes et al (2013) also observed less feeding time, and less time standing and more time lying, for more efficient animals.…”
Section: Discussionmentioning
confidence: 74%
“…Residual feed intake (RFI) is a measure of feed efficiency that permits to identify animals with similar performance but that differ in terms of energy requirements for maintenance and production. Evidence from beef cattle indicates that more efficient animals spent less time at the feed bunk than less efficient animals (GOMES et al, 2013;GUIMARÃES et al, 2017;KELLY et al, 2010), possibly saving energy in this activity and spending more time in sedentary activities. Furthermore, a higher feed efficiency of animals might be associated with less stress and lower circulating cortisol concentrations (GOMES et al, 2013;LLONCH et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Ingestive behavior traits allow for determining feeding patterns, which have been described to be strongly correlated with feed efficiency traits [ 15 , 16 ]. Positive and moderate phenotypic correlations between feeding behavior and RFI have been reported [ 5 , 9 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Positive and moderate phenotypic correlations between feeding behavior and RFI have been reported [ 5 , 9 , 17 ]. Studies have shown that high-efficiency animals (low RFI) spend less time on feed-related activities than low-efficiency animals (high RFI) [ 15 , 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating four traits used in feed efficiency tests (ADG, DMI, feed conversion ratio, and RFI), ARCHER et al (2000) and WANG et al (2006) showed that ADG is the most variable trait, a fact that may explain the low correlation estimated in the present study between ADG in the two consecutive phases. GUIMARÃES et al (2017), evaluating Senepol cattle in two consecutive feed efficiency tests at yearling, also reported a correlation close to zero between ADG values and a high correlation between DMI and BW 0.75 . However, in contrast to the present study, the authors observed high correlations between the other feed efficiency traits (except for FC) and ingestive behavior obtained in the two phases (yearling and long yearling).…”
Section: Discussionmentioning
confidence: 79%